(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article studies development ways of dividend policy in companies. Moreover, balance between retained earnings and dividend payouts and integrating risk management into dividend strategy are analyzed. Scientific conclusions and recommendations are presented on the basis of analyses.